2014
DOI: 10.1080/10256016.2015.987275
|View full text |Cite
|
Sign up to set email alerts
|

A study of the characteristics of karst groundwater circulation based on multi-isotope approach in the Liulin spring area, North China

Abstract: Due to the significance of karst groundwater for water supply in arid and semi-arid regions, the characteristics of the karst groundwater flow system in the Liulin spring area, North China, are analysed through isotopic tracing (δ(2)H, δ(18)O, δ(13)C and (3)H) and dating approaches ((14)C). The results show that the primary recharge source of karst groundwater is precipitation. Evaporation during dropping and infiltration of rainfall results in a certain offset in the values of δ(2)H and δ(18)O in groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Like tritium, radiocarbon activities are usually analyzed to quantify groundwater ages (Kalin, ). Radiocarbon‐based groundwater ages have been applied to quantify groundwater migration rates (Ajami et al, ; Carreira et al, ; Hanshaw et al, ; Tenu et al, ; Zang et al, ), map recharge zones and rates (e.g., Hoque & Burgess, ; Leaney & Allison, ), assess groundwater discharges to rivers (Bourke et al, ), identify surface‐borne contaminant sources (e.g., Dodo & Zuppi, ; Heaton et al, ; Osenbrück et al, ), and understand geogenic contaminant sources and mobilization mechanisms (e.g., fluoride—Silva et al, —and arsenic—Gonzalez Hita et al, ).…”
Section: Isotope Hydrogeologymentioning
confidence: 99%
“…Like tritium, radiocarbon activities are usually analyzed to quantify groundwater ages (Kalin, ). Radiocarbon‐based groundwater ages have been applied to quantify groundwater migration rates (Ajami et al, ; Carreira et al, ; Hanshaw et al, ; Tenu et al, ; Zang et al, ), map recharge zones and rates (e.g., Hoque & Burgess, ; Leaney & Allison, ), assess groundwater discharges to rivers (Bourke et al, ), identify surface‐borne contaminant sources (e.g., Dodo & Zuppi, ; Heaton et al, ; Osenbrück et al, ), and understand geogenic contaminant sources and mobilization mechanisms (e.g., fluoride—Silva et al, —and arsenic—Gonzalez Hita et al, ).…”
Section: Isotope Hydrogeologymentioning
confidence: 99%
“…By applying geological statistics, Piper diagrams and hydrogeochemical simulation techniques, Wang et al [14,15] and Ma et al [16][17][18] obtained hydrological information on the surface water and groundwater and depicted karst groundwater chemical characteristics in the Liulin spring area. Zang et al [19,20] traced the source of major ions in karst groundwater using isotopic tracing techniques and hydrogeochemical methods. There were hardly any studies focused on hydrogeochemical processes of karst groundwater from rainfall infiltration in recharge area to forming higher Total Dissolved Solids (TDS) groundwater in stagnant area.…”
Section: Introductionmentioning
confidence: 99%
“…Such binary mixing with centennial groundwater is F I G U R E 8 Hydrogeological conceptual model of Jarastepar aquifer, showing the evolution of EC, Mg 2+ , and groundwater age, as well as the main geochemical and mixing processes. Lithology explanation in Figure 2 normally observed in large carbonate aquifers, often partially confined, in which a long-tailed age distribution is defined (Jiang et al, 2019;Toth & Katz, 2006;Yager et al, 2010;Zang et al, 2015). The Jarastepar aquifer is far from that definition-its outcropping surface is 56 km 2 , mostly corresponding to the unconfined EZ, and can be rapidly drained through the overflow springs.…”
Section: Implications Of the Geological Setting On The Groundwater mentioning
confidence: 97%
“…Several studies have demonstrated the applicability of environmental tracers for groundwater dating in karst systems, shedding light on flow dynamics involving recently infiltrated water and older groundwater components. The latter fraction in the mix may be a few decades old (Delbart et al, 2014;Jiang, Guo, & Tang, 2019), yet more commonly was infiltrated before the middle of the 20th Century, before the anthropogenic release of 3 H and CFCs (Han et al, 2007;Long & Putnam, 2009;Toth & Katz, 2006;Yager et al, 2010;Zang, Zheng, Qin, & Jia, 2015). In regional carbonate aquifers, some partially confined, dating old groundwater components can give ages of hundreds or even thousands of years (Land & Huff, 2010;Müller et al, 2016;Musgrove et al, 2019;Plummer, Busby, Lee, & Hanshaw, 1990;Xanke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%